Penerapan Balanced Scorecard (BSC) Untuk Pengukuran Kinerja Pada PT Timtim Natural - Kristanto, Nathania (Jurnal Ekonomi, Manajemen dan Akuntansi (JEKMA), 2025)
This study aims to design and evaluate the performance of PT Timtim Natural using the balanced scorecard approach with a qualitative descriptive method through interviews and documentation studies. The design was carried out by aligning the company's vision and mission with the four perspectives of the BSC. The results show that the company has excellent financial performance, but customer acquisition remains low despite high retention rates. The internal business process perspective is rated as good thanks to regular evaluations, while the learning and growth perspective is rated as fairly good despite challenges related to infrastructure updates and human resource adaptation, most of whom are older in age.